Kajian tentang kemandirian lembaga kepolisian dalam penegakan hukum pada era reformasi - Sri Hartini (Universitas Negeri Yogyakarta, 2010)
Law enforcement is a condition sine qua non for the implementation of democracy. It is necessary to maintain law order, secure political decision making processes, guarantee individual freedom, and protect human rights. Beside, in the context of law enforcement process, the independence of judiciary system is needed for materialization of the principle of law based State. The judiciary system will be independent as long as the stake holders of that institution are independent and truth and justice oriented. The independence of the police institution as sub-system of the judiciary is necessary in the investigation of crime. Normatively it was recognized that the police is institutionally independent and separated from the TNI since 1 July 2000, by the promulgation of the People Assembly Number: VI/MPR/2000 and Act Number: 2/2002 on Indonesian Police. However, in operational level there are external and internal shortcomings. Internal shortcomings meant are the behavior of the criminal investigator police which are not transparent, militaristic, unprofessional, discriminative, and tends to use violent actions. External shortcomings are problem related to the existence of legal instruments, vertical and horizontal intervention from the colleagues, public, “old brother”, and limited budget and facilities to support investigation process. The independence of the police as the criminal investigating institution in the criminal justice system requires supporting aspects such as available legal instrument, well organization, political will of the government, capable human resources, budget, means, personal investigating police and cultural aspect of criminal investigating police as civilian police. Therefore the works of the criminal investigating police have to be reported to the concerned victims. Apart from that exist legal instruments such as the law criminal procedure and related regulations have to be reviewed an amended.